ANALISIS KESELAMATAN PELAYARAN DITINJAU DARI KEPUASAN KERJA DAN STRES KERJA DENGAN KINERJA PELAUT SEBAGAI VARIABEL INTERVENING (STUDI PADA PELAUT ALUMNI BP2IP TANGERANG PERIOD 2014-2018) - Indah Purnaningratri; Syairi Anwar; Dwi Endah Kurniasari; Hari Mochamad Mansur (Institute of Computer Science (IOCS), 2022)
The purpose of this research is to analyse the effects of job satisfaction and work stress on shipping safety with job performance of seafarers being intervening variable. Using these variables, for instance Parker et al (2002), discovered effect job satisfaction and work stress toward job performance of seafarers to increase shipping safety. The study was conducted at Tangerang Merchant Marine Collegues (TMMC), the sample size is 93 seafarers who work in many shipping company. Data is processed using Path Analysis which assisted by application program of Statistical Package for Social Science (SPSS) version 25.0. The results show that job satisfaction has directed effect to 3,24% of job performance of seafarers and work stress has directed effect to 66,59% of job performance of seafarers. While job satisfaction has indirect effect to 17,87% of shipping safety through job performance of seafarers and work stress has indirect effect to 81,03% of shipping safety through job performance of seafarers, job performance of seafarers has directed effect to 98% of shipping safety. The results from Path Analysis indicated that work stress is higher effect on job performance of seafarers than job satisfaction and job performance of seafarers is the highest directly effect on shipping safety.